2018
DOI: 10.19080/jdvs.2018.06.555696
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tidal River Management on Livestock in the Ganges-Brahmaputra Basin

Abstract: Ganges-Brahmaputra Basin provides several wetlands which are resourceful for rearing livestock as to support coastal community and their livelihoods in the Southwest Bengal delta. Water-logging hampers rural livelihood by damaging agricultural crops, plant, trees, grazing land and reducing livestock. Primarily, Tidal River Management (TRM) is introduced by coastal community to manage tidal river-floodplain ecosystem by way of removing water-logging, increasing navigability of tidal river, improving agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The resulting sediment deposition raised land surface of the beels inside the polders substantially by 0.2-1 m, but with large spatial variation in deposited amounts within a beel (Gain et al, 2017). Al Masud et al (2018) reported higher food productivity and household income from livestock at former TRM sites compared with elsewhere in the region. Since TRM results in a rise of the polder land surface, it may provide an opportunity to elevate and maintain land above future sea level in other sinking deltas around the world as well, when there is sufficient fluvial or estuarine sediment available (Brown et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting sediment deposition raised land surface of the beels inside the polders substantially by 0.2-1 m, but with large spatial variation in deposited amounts within a beel (Gain et al, 2017). Al Masud et al (2018) reported higher food productivity and household income from livestock at former TRM sites compared with elsewhere in the region. Since TRM results in a rise of the polder land surface, it may provide an opportunity to elevate and maintain land above future sea level in other sinking deltas around the world as well, when there is sufficient fluvial or estuarine sediment available (Brown et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This flooding was more closely researched, and investigators found that income levels and food security level increased for most groups after TRM (Edrish, Yeasmin, & Rahman, ; Mutahara, ). Households own more livestock after TRM, particularly ducks and chickens (Masud, ).…”
Section: Tidal River Managementmentioning
confidence: 99%
“…This region is the home of millions of people but the coastline is mostly irregular and consist of a series of river and canal network which continuously changing their courses, flow velocity and natural land formation [12][13][14]. Conversely, this area is the hub of recurrent hydro-climatic disasters, erratic rainfall and temperature change, water logging, salinity intrusion, diverse land use changes [15,16] and competitive resource consumption pattern [17][18][19].…”
Section: Introductionmentioning
confidence: 99%